2014
DOI: 10.1038/srep06114
|View full text |Cite
|
Sign up to set email alerts
|

An Electrically Switchable Metal-Organic Framework

Abstract: Crystalline metal organic framework (MOF) materials containing interconnected porosity can be chemically modified to promote stimulus-driven (light, magnetic or electric fields) structural transformations that can be used in a number of devices. Innovative research strategies are now focused on understanding the role of chemical bond manipulation to reversibly alter the free volume in such structures of critical importance for electro-catalysis, molecular electronics, energy storage technologies, sensor device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
60
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 37 publications
5
60
2
1
Order By: Relevance
“…Cu:TCNQ can grow into two phases. [22] The above discussion shows that electric field can act as a tool to alter the structure and electrical properties in Cu:TCNQ. While, in the lower conductivity Phase-II the metal coordination is more tetrahedral.…”
Section: Introductionmentioning
confidence: 91%
“…Cu:TCNQ can grow into two phases. [22] The above discussion shows that electric field can act as a tool to alter the structure and electrical properties in Cu:TCNQ. While, in the lower conductivity Phase-II the metal coordination is more tetrahedral.…”
Section: Introductionmentioning
confidence: 91%
“…An electric field has good controllability, but the structural switching of MOFs induced by an electric field is very rare . The electric field has emerged in recent years as a new stimulating source that can induce RPT of MOFs.…”
Section: Different External Stimulimentioning
confidence: 99%
“…Fernandez et al reported the switchable Cu(TCNQ) MOF, which can be reversibly transformed between a high-resistance state and a conducting state by the application of an external potential. 24 These works have demonstrated the potential of MOFs for incorporation into future electronic devices. MOFs could provide superior functionalities to devices based on traditional inorganic materials, due to their extraordinarily tuneable and adaptable chemical structures and porosities, which provides a vast design palette for the tuning of MOF electronic properties.…”
Section: Introductionmentioning
confidence: 96%